Improvement of Physical Activity by a Kiosk-based Electronic Screening and Brief Intervention in Routine Primary Health Care: Patient-Initiated Versus Staff-Referred - Leijon, Matti; Arvidsson, Daniel; Nilsen, Per; Stark Ekman, Diana; Carlfjord, Siw; Andersson, Agneta; Johansson, Anne Lie; Bendtsen, Preben (JMIR Publications, 2011)
BackgroundInteractive behavior change technology (eg, computer programs, Internet websites, and mobile phones) may facilitate the implementation of lifestyle behavior interventions in routine primary health care. Effective, fully automated solutions not involving primary health care staff may offer low-cost support for behavior change. ObjectivesWe explored the effectiveness of an electronic screening and brief intervention (e-SBI) deployed through a stand-alone information kiosk for promoting physical activity among sedentary patients in routine primary health care. We further tested whether its effectiveness differed between patients performing the e-SBI on their own initiative and those referred to it by primary health care staff. MethodsThe e-SBI screens for the physical activity level, motivation to change, attitudes toward performing the test, and physical characteristics and provides tailored feedback supporting behavior change. A total of 7863 patients performed the e-SBI from 2007 through 2009 in routine primary health care in Östergötland County, Sweden. Of these, 2509 were considered not sufficiently physically active, and 311 of these 2509 patients agreed to participate in an optional 3-month follow-up. These 311 patients were included in the analysis and were further divided into two groups based on whether the e-SBI was performed on the patient´s own initiative (informed by posters in the waiting room) or if the patient was referred to it by staff. A physical activity score representing the number of days being physically active was compared between baseline e-SBI and the 3-month follow-up. Based on physical activity recommendations, a score of 5 was considered the cutoff for being sufficiently physically active. ResultsIn all, 137 of 311 patients (44%) were sufficiently physically active at the 3-month follow-up. The proportion becoming sufficiently physically active was 16/55 (29%), 40/101 (40%), and 81/155 (52%) for patients with a physical activity score at baseline of 0, 1 to 2, and 3 to 4, respectively. The patient-initiated group and staff-referred group had similar mean physical activity scores at baseline (2.1, 95% confidence interval [CI] 1.8-2.3, versus 2.3, 95% CI 2.1-2.5) and at follow-up, (4.1, 95% CI 3.4-4.7, vs 4.2, 95% CI 3.7-4.8). ConclusionsAmong the sedentary patients in primary health care who participated in the follow-up, the e-SBI appeared effective at promoting short-term improvement of physical activity for about half of them. The results were similar when the e-SBI was patient-initiated or staff-referred. The e-SBI may be a low-cost complement to lifestyle behavior interventions in routine primary health care and could work as a stand-alone technique not requiring the involvment of primary health care staff.